High-performance nanogenerators based on flexible cellulose nanofibril/MoS2 nanosheet composite piezoelectric films for energy harvesting. (February 2021) - Wu, Tao; Song, Yiheng; Shi, Zhuqun; Liu, Dongning; Chen, Siling; Xiong, Chuanxi; Yang, Quanling
Abstract: High-performance and environment-friendly biomass-based piezoelectric films have drawn much attention recently. Here, 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofibril (TOCN)/molybdenum disulfide (MoS2 ) nanosheet bionanocomposite piezoelectric films were prepared through an environmentally benign pathway by aqueous dispersion. The TOCN/MoS2 nanocomposite films exhibited good mechanical properties with the highest Young's modulus of 8.2 GPa and tensile strength of 307 MPa. When the MoS2 content was 4 wt%, the longitudinal piezoelectric constant ( d 33 ) of the composite film reached a maximum value of 31 pC/N, much higher than 12 pC/N of the neat TOCN film and other reported cellulose-based piezoelectric films. Moreover, nanogenerators fabricated from TOCN/MoS2 composite films exhibited a maximum output voltage of 4.1 V and a short-circuit current of 0.21 μA. Furthermore, the current generated by the nanogenerator was rectified and converted to direct current. A 10 μF commercial capacitor was charged to 1.6 V at 120 s, indicating the ability to collect mechanical energy generated in the natural environment. Therefore, the TOCN/MoS2 composite films are promising in the field of piezoelectric materials and nanogenerators. Graphical Abstract: Flexible TOCN/MoS2 composite films with high piezoelectric performance are promising in smart piezoelectric nanogenerator for energy harvesting. ga1 Highlights: TOCN/MoS2 nanocomposite films exhibit excellent piezoelectric property ( d 33 =31 pC/N). TOCN/MoS2 nanocomposite films do not contain the heavy metals present in traditional piezoelectric materials. The mechanical strength of the TOCN/MoS2 nanocomposite film is extremely good. The flexible TOCN/MoS2 PENG can be used for efficient energy harvesting.